2015
DOI: 10.1038/srep11660
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of multipotent postnatal stem cells from human maxillary sinus membrane

Abstract: Maxillary sinus membrane (MSM) elevation is a common surgical technique for increasing bone height in the posterior maxilla prior to dental implant placement. However, the biological nature of bone regeneration in MSM remains largely unidentified. In this study, MSM tissue was obtained from 16 individuals during orthognathic surgery and used to isolate MSM stem cells (MSMSCs) by single-colony selection and STRO-1 cell sorting. The cell characteristics in terms of colony-forming ability, cell surface antigens, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 38 publications
2
40
0
1
Order By: Relevance
“…Normal human MSM samples were obtained as previously reported6. MSMSCs were isolated and cultured as previously reported6.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Normal human MSM samples were obtained as previously reported6. MSMSCs were isolated and cultured as previously reported6.…”
Section: Methodsmentioning
confidence: 99%
“…MSMSCs were isolated and cultured as previously reported6. BMSSCs were obtained from ScienCell Research Laboratory (San Diego, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical studies have shown that maxillary sinus augmentation can be reached by elevating the MSM with or without grafting, which suggested that maxillary sinus membrane possesses osteogenic activity. Further studies have isolated and characterized maxillary sinus membrane stem cells (MSMSCs) in maxillary sinus membrane, which displayed stem cell properties similar to bone marrow mesenchymal stem cells (BMMSCs) . Our previous study demonstrated that MSMSCs could express MSC markers such as STRO‐1, CD146, CD29.…”
Section: Introductionmentioning
confidence: 99%